2010
DOI: 10.1002/ar.21309
|View full text |Cite
|
Sign up to set email alerts
|

The Sealed Osteons of Cortical Diaphyseal Bone. Early Observations Revisited With Scanning Electron Microscopy

Abstract: The frequency, structure, mode of formation and significance of sealed osteons remain unsettled. Sealed osteons have been reported as an unusual finding in the cortical bone of experimental animals: we extended the observation to human cortical bone studied with SEM. Tibial bone specimens from three patients who sustained a traumatic below-the-knee amputation were used in the study. The observed total mean density of osteons was 19.25/mm 2 and the percentage of sealed and partially sealed osteons was 4.2% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 15 publications
1
27
1
Order By: Relevance
“…Another way for an osteon to discontinue transpires within the mid‐cortex itself through relatively rare occurrences called ‘blind’ or sealed osteons (Koltze, ; Cohen & Harris, ; Congiu & Pazzaglia, ). In three dimensions, blind osteons gradually become narrower before they end.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way for an osteon to discontinue transpires within the mid‐cortex itself through relatively rare occurrences called ‘blind’ or sealed osteons (Koltze, ; Cohen & Harris, ; Congiu & Pazzaglia, ). In three dimensions, blind osteons gradually become narrower before they end.…”
Section: Discussionmentioning
confidence: 99%
“…). Studies suggest diverse reasons for the occurrence of blind osteons, as for example a relationship to necrotic vessels making them evidence for the dynamic requirements of intracortical blood flow (Schumacher, ; Koltze, ; Cohen & Harris, ; Congiu & Pazzaglia, ) and/or trauma (Henrie et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Sealed + partially sealed osteons were much less frequent in the non‐human bones (< 0.1 vs. 1.8% in human femora, n = 30) despite comparatively equivalent and often higher OPD compared with the human bones we examined. Congiu & Pazzaglia () reported that the percentage of sealed and partially sealed osteons from amputated tibiae from three patients (ages 25, 28, and 52 years) was 4.2 and 1.7%, respectively. However, in a later study of tibial and femoral mid‐diaphyses from four healthy young males (ages 25, 28, 30, and 32) who underwent amputations because of traumatic limb injuries, they found that only 2.2% of the total osteons were sealed (Pazzaglia et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that increases in the prevalence of sealed osteons might reflect reduced bone quality which can accompany ischemia that presumably accompanies progressive remodeling seen with age in humans (Congiu & Pazzaglia, ; Pazzaglia et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation